2018
DOI: 10.4103/ua.ua_190_17
|View full text |Cite
|
Sign up to set email alerts
|

Complications of 411 laparoscopic urological procedures: A single surgeon experience

Abstract: Objectives:The aim of this study is to review the complications of laparoscopic urological procedures performed using a single surgeon during a 12-year period.Materials and Methods:From June 2004 to May 2017, a total of 411 abdominal urological procedures were performed using the author. They included 250 varicocele ligations, 94 nephrectomies (simple, partial, radical, and nephroureterectomy), 34 adrenalectomies, 22 renal cyst ablation, and 11 pelvic lymph node dissections. Operative and postoperative complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In a study made by Daggülü et al in our country, open surgery passing ratio was reported as 5% (17). In a current study on 411 cases containing different urological laparoscopic procedures, total complication ratio was found 13.4% (18). In the series of Demirel et al containing 228 cases, major vascular injury which is a major complication was found 3.5% and organ injury was 0.87% (19).…”
Section: Discussionmentioning
confidence: 56%
“…In a study made by Daggülü et al in our country, open surgery passing ratio was reported as 5% (17). In a current study on 411 cases containing different urological laparoscopic procedures, total complication ratio was found 13.4% (18). In the series of Demirel et al containing 228 cases, major vascular injury which is a major complication was found 3.5% and organ injury was 0.87% (19).…”
Section: Discussionmentioning
confidence: 56%
“…[31] As for LD therapy, vessels damage and subcutaneous emphysema might happen to patients during the process of cyst ablation and establishing pneumoperitoneum. [32] The limited included studies in our meta-analysis and the heterogeneity of some date were two main limitations of this study. Due to the lack of researches on the comparations between AS and LD, we included six articles merely and the patient selection bias, heterogeneity of cyst diameter and follow up time or difference of operator training/experience could also be limitations.…”
Section: Discussionmentioning
confidence: 92%
“…Other authors report more blood loss, mainly related with the greater complexity of the surgical technique. (16) In an initial study of 200 cases, Rassweiler et al (4) reported 7.5% conversion to open surgery, Gill et al (17) 6.6%, Srivastava et al (3) 3.2%, whereas Al-Otabi et al (18) informed 0.7%. (3,18) Conversion to open surgery is not, necessarily, considered a complication, but it does reflect the learning curve of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…(16) In an initial study of 200 cases, Rassweiler et al (4) reported 7.5% conversion to open surgery, Gill et al (17) 6.6%, Srivastava et al (3) 3.2%, whereas Al-Otabi et al (18) informed 0.7%. (3,18) Conversion to open surgery is not, necessarily, considered a complication, but it does reflect the learning curve of the surgeon. In the study, males, past history of prior surgery, operative time and bleeding turned out to be predictive factors for conversion to open surgery.…”
Section: Discussionmentioning
confidence: 99%